Leveraging Ontology-based Systems through Continuous Ontology Engineering - Salamon, Jordana Sarmenghi; Arias, Paola Espinoza; Barcellos, Monalessa Perini (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248312, 2026)
Research Context: Ontologies have been recognized as key enablers of digital transformation in industry. They are used to assign semantics to information items, supporting data and knowledge management based on a common and shared understanding and representation. They play a paramount role in the Semantic Web and the implementation of Linked Open Data (LOD). Scientific and/or Practical Problem: Developing and maintaining ontologies may be complex, time-consuming, and resource-intensive. Additionally, traditional sequential ontology engineering methods often fail to address industrial needs such as changing requirements and time constraints. Iterative approaches mitigate some challenges but are not always sufficient. Proposed Solution and/or Analysis: To align ontology development with information systems development, both processes must be integrated. An end-to-end flow that integrates and supports ontology engineering from conception to operation is required to enable a continuous and industry-aligned process. We propose the use of a Continuous Ontology Engineering (COE) approach. We define principles that characterize COE, report on its adoption in a multinational chemical company, and share lessons learned. Related IS Theory: This work relates to the organizational knowledge creation theory. Ontologies structure and organize knowledge, help capture tacit knowledge and transform it into explicit, enabling knowledge integration into information systems and supporting open data publication. Research Method: We conducted a participative case study to investigate the use of COE. Summary of Results: Findings suggest that COE contributes to aligning ontology and information system development. However, challenges remain, such as the lack of comprehensive and integrated tool support. Contributions and Impact to IS area: For researchers, this work advances the state of the art in a novel and relevant topic for developing knowledge-based systems, Semantic Web, and LOD solutions. For practitioners, it offers knowledge about COE and an example that may inspire organizations to implement COE practices to align ontology and information systems development.